2017
DOI: 10.1093/humrep/dex239
|View full text |Cite
|
Sign up to set email alerts
|

Use of the serum anti-Müllerian hormone assay as a surrogate for polycystic ovarian morphology: impact on diagnosis and phenotypic classification of polycystic ovary syndrome

Abstract: No external funding. The authors have no conflict of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 31 publications
1
52
1
1
Order By: Relevance
“…A limitation of this approach was that the diagnosis of PCOS did not include PCOM, and it is possible that some HA-EM women with normal AMH levels did have PCOM. Nevertheless, our AMH threshold for PCOM was similar to those established in women with ultrasonographically determined PCOM (32,33,43). Second, waist measurements to assess body fat topography were missing in a substantial number of women.…”
Section: Discussionsupporting
confidence: 79%
“…A limitation of this approach was that the diagnosis of PCOS did not include PCOM, and it is possible that some HA-EM women with normal AMH levels did have PCOM. Nevertheless, our AMH threshold for PCOM was similar to those established in women with ultrasonographically determined PCOM (32,33,43). Second, waist measurements to assess body fat topography were missing in a substantial number of women.…”
Section: Discussionsupporting
confidence: 79%
“…The higher AMH levels in phenotype A than in phenotype C or D partly explain the unusually high AMH levels found in the PCOS group in its whole, compared with other studies. This difference is probably not related to the type of assay used because it has been shown that the results obtained with this assay can be superimposed on those of other manual assays .…”
contrasting
confidence: 46%
“…Rotterdam criteria recognize four PCOS phenotypes: classic PCOS with (type A) and without (type B) polycystic ovaries, ovulatory PCOS (type C) without intermittent or absent cycles, and "non-hyperandrogenic" PCOS (type D) without high T or excessive body hair [1,3]. Phenotype B, however, will likely be subsumed within Type A when three-dimensional ovarian ultrasonography and standardized AMH immunoassays become widely available enabling accurate characterization of polycystic ovaries [9]. So, in essence, PCOS comprises three distinct phenotypes.…”
Section: Introductionmentioning
confidence: 99%